Satu Langkah Penting: Kebijakan Timor Leste Menyepakati MoU Join Ministerial Statement dengan Indonesia Tahun 2002 - FITHRIA, FARAH AGNIS (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2024)
Abstract This article will discuss the cooperation established by Timor Leste and Indonesia in 2002 through the MoU Joint Ministerial Statement. Timor Leste is a country that has been occupied by Indonesia for 24 years, and during that time there was a lot of treatment from the Indonesian government which was felt to be a stepchild of Timor Leste and gave the impression that it paid little attention to that country. Because of this, the people of Timor Leste protested with demonstrations demanding separation from Indonesia. However, not long after officially becoming an independent country, Timor Leste adopted a policy to agree to open diplomatic relations with Indonesia. Based on the brief explanation above, the author formulates the research question as: Why did Timor Leste agree to sign a Memorandum of Understanding on the Joint Ministerial Statement with Indonesia in 2002? This article will use qualitative and analytical descriptive methods with research library data collection techniques where the data obtained comes from books, reputable scientific articles and the internet. The theory that the author will use is the Decision Making Theory. Keywords: Timor Leste; Indonesia; foreign policy; Cooperation ABSTRAK Artikel ini akan membahas tentang kesepakatan kerjasama yang di bangun oleh Timor Leste dan Indonesia pada tahun 2002 melalui MoU Joint Ministerial Statement. Timor Leste adalah negara yang telah diduduki oleh Indonesia selam 24 tahun, dan selama itu banyak perlakuan dari pemerntah Indonesia yang di rasa menganak tirikan Timor Leste dan terkesan kurang memperhatikan negara itu. Karena hal ini masyarakat Timor Leste melakukan protes dengan demonstrasi menuntut pemisahan dari Indonesia. Namun tidak berselang lama setelah resmi menjadi negara yang merdeka, Timor Leste mengambil sebuah kebijakan untuk menyepakati membuka hubungan diplomatik dengan Indonesia. Berdasarkan penjelasan singkat diatas maka penulis merumuskan pertanyaan penelitian menjadi: Mengapa Timor Leste menyepakati penandatangan nota kesepahaman Joint Ministerial Statement dengan Indonesia pada tahun 2002? Tulisan ini akan menggunakan metode kualitatif dan bersifat deskriptif analitis dengan teknik pengumpulan data library reaserch di mana data-data yang diperoleh bersumber dari buku-buku, artikel ilmiah bereputasi maupun internet. Teori yang akan dipakai penulis adalah Teori Decision making Process. Kata Kunci: Timor Leste; Indonesia; Kebijakan Luar Negeri; Kerjasama